Is a very high public debt a problem? - Pedro Le\~ao (Levy Economics Institute of Bard College, 2015)
This paper has two main objectives. The first is to propose a policy architecture that can prevent a very high public debt from resulting in a high tax burden, a government default, or inflation. The second objective is to show that government deficits do not face a financing problem. After these deficits are initially financed through the net creation of base money, the private sector necessarily realizes savings, in the form of either government bond purchases or, if a default is feared, 'acquisitions' of new money.
Keywords: E12; E42; E52; E62; E63; 330; Fiscal Policy; Functional Finance; Modern Monetary Theory; Monetary Policy; Public Debt Sustainability; Zero Interest Rates